Cancer nanotheranostics in the second near‐infrared window. Issue 1 (12th September 2020) - Jiang, Shanshan; Huang, Kai; Qu, Junle; Lin, Jing; Huang, Peng
Abstract: Nanotheranostics is an attractive and fast developing nanomedicine technology that integrates both diagnostics and therapeutics in a single nanoplatform. It ensures consistent spatiotemporal distribution and uniform targeting of the imaging and therapeutic agents, thus desirable for real‐time monitoring of in situ therapeutic effects and long‐term tailorable therapeutics in accordance to disease prognosis for personalized medicine. Optical stimuli of nanotheranostics offer easy and precise controllability to combat cancer. Compared with the conventional use of visible and the first near‐infrared region light, using the second near‐infrared (NIR‐II) region light as the incident excitation enables cancer nanotheranostics to go deeper and with enhanced theranostic efficiency. Realizing the extraordinary advantages of accomplishing cancer nanotheranostics in the NIR‐II region, burgeoning research efforts were devoted to this field. This review aims to analyze the available imaging and therapeutic approaches to realize nanotheranostics in the NIR‐II region, and to summarize the current applications of cancer nanotheranostics in the NIR‐II region. In the end, we will discuss the challenges and outlook on the possible perspectives in the field. Abstract : Cancer nanotheranostics in the second near‐infrared window integrates diagnostics and therapeutics simultaneously to realize more efficient cancer treatment in deep tissue.